2005
DOI: 10.1002/hed.20172
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life as predictor of weight loss in patients with head and neck cancer

Abstract: Patients with head and neck cancer who are at risk of severe weight loss developing during treatment may be detected with the aid of HRQL questionnaires at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 21 publications
6
74
0
Order By: Relevance
“…Lastly, multivariate analyses are not always performed. 8,21,23 To our knowledge, our study is 1 of the largest cohort studies conducted among early stage HN cancer patients. The characteristics of the patients and of their disease were systematically and prospectively collected using validated, structured questionnaires.…”
Section: Weight Loss In Head Andmentioning
confidence: 95%
See 2 more Smart Citations
“…Lastly, multivariate analyses are not always performed. 8,21,23 To our knowledge, our study is 1 of the largest cohort studies conducted among early stage HN cancer patients. The characteristics of the patients and of their disease were systematically and prospectively collected using validated, structured questionnaires.…”
Section: Weight Loss In Head Andmentioning
confidence: 95%
“…At the time of diagnosis, critical weight loss is more frequently observed in patients with cancer of the hypopharynx, oropharynx/ oral cavity, or supraglottic larynx. 6,8,23,44 In the literature, the early stages (I or II) are generally compared with advanced stages (III or IV), and the comparisons show that advanced stage HN cancer patients are more likely to experience weight loss and consequently to receive enteral nutrition. 19 Our study found that differences in weight loss are observed during the early stages.…”
Section: Weight Loss In Head Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of nutritional risk in hospitalized patients with cancer in our study was higher than that reported in those studies in European and American hospitals by using the same parameters. 3,6,[18][19][20][21][22][23][24][25][26][27][28][29] It indicates that compared with cancer patients from European and American countries, there is a higher proportion of Chinese cancer patients at nutritional risk and with nutritional deficiencies at admission and during hospitalization. The possible reasons for this difference include: (1) compared with cancer patients in Western countries, the Chinese patients has relatively lower body weight and poor nutritional status at admission, and (2) relatively fewer doctors in Chinese hospitals can identify cancer patients at nutritional risk early in order to plan Nutritional risk, clinical outcome and quality of life in cancer patients K Yu et al the best possible intervention, which make the patients' nutritional status tended to worsen during the hospitalization.…”
Section: Suitability Of Nrs-2002 In Patients With Cancermentioning
confidence: 99%
“…Similarly, food intake -one of the major determinants of nutritional status -appears to influence QoL, as a correlation between them exists (21). Moreover, a low QoL is associated with nutrition-related symptoms and weight loss (22).…”
Section: Interactions Between Qol and Nutritional Status Of The Patiementioning
confidence: 99%